PENGARUH POLA ASUH ORANG TUA DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA SD KELAS V DI SD NEGERI MUARA BOLAK 4 KEC. SOSORGADONG. - REGINA SIPAYUNG (LP2MTBM MAKARIOZ, 2018)
This research is a kind of quantitative research with correlation technique. Correlation techniques are used to test the hypothesis to find the relationship between two variables. Population in this research is all elementary school student of Class V in Elementary School of Muara Bolak 4 Kec. Sosorgadong as many as 60 students. This study is a population study. So that all students of class V become respondents. Data collection using questionnaires or questionnaires to find out the pattern of parent care and student discipline, while the method of observation and documentation used for data collection in the form of a list of students and the picture of Elementary School Grade V in Elementary School Muara Bolak 4 Kec. Sosorgadong. Research data that has been collected and then analyzed by using statistical analysis techniques, Testing research hypothesis using product moment formula. The results showed that the parenting pattern of elementary school students in grade V SD Muara Bolak 4 Kec. Sosorgadong with an average score of 70.11 included into the category